2022
DOI: 10.1111/ejn.15616
|View full text |Cite
|
Sign up to set email alerts
|

EEG alpha and pupil diameter reflect endogenous auditory attention switching and listening effort

Abstract: Everyday environments often contain distracting competing talkers and background noise, requiring listeners to focus their attention on one acoustic source and reject others. During this auditory attention task, listeners may naturally interrupt their sustained attention and switch attended sources. The effort required to perform this attention switch has not been well studied in the context of competing continuous speech. In this work, we developed two variants of endogenous attention switching and a sustaine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Effortful listening to speech in noise engages heightened arousal as well as increased demands on attention, working memory, and linguistic processing (Peelle, 2018). Unravelling these various aspects - in particular separating arousal-related effects from those related to the allocation of cognitive resources - is a key challenge for the field (Zekveld et al, 2014; White & Langdon, 2021; Ritz et al, 2021; Haro et al, 2022; McGarrigle et al, 2021). Correlations between subjective, behavioral, and physiological measures of listening effort have not always yielded consistent results (Alhanbali et al, 2019), implying that different approaches may be capturing distinct facets of this construct.…”
Section: Introductionmentioning
confidence: 99%
“…Effortful listening to speech in noise engages heightened arousal as well as increased demands on attention, working memory, and linguistic processing (Peelle, 2018). Unravelling these various aspects - in particular separating arousal-related effects from those related to the allocation of cognitive resources - is a key challenge for the field (Zekveld et al, 2014; White & Langdon, 2021; Ritz et al, 2021; Haro et al, 2022; McGarrigle et al, 2021). Correlations between subjective, behavioral, and physiological measures of listening effort have not always yielded consistent results (Alhanbali et al, 2019), implying that different approaches may be capturing distinct facets of this construct.…”
Section: Introductionmentioning
confidence: 99%
“…Two additional metrics that are associated with reduced sustained attention and were hypothesized to be increased in the ADHD group are level of alpha power and the frequency of spontaneous gaze-shifts. Higher alpha power is associated with reduced levels of attention/arousal, and alpha power is consistently found to increase in conditions of boredom, tiredness or prolonged time on tasks (Clarke et al, 2001; Dockree et al, 2007; Palva and Palva, 2007; Wöstmann et al, 2017; Boudewyn and Carter, 2018; Jin et al, 2019; Haro et al, 2022). Several studies have also found higher baseline alpha power in individuals with ADHD vs. controls (Barry et al, 2003; Johnstone et al, 2013; Bozhilova et al, 2022; Michelini et al, 2022), however results are not always consistent (Loo and Makeig, 2012; Johnstone et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In future AAD studies with moving talkers, a higher degree of temporal resolution can be achieved by asking the subjects also to report the spatial trajectory of the conversation followed. Additionally, further research is needed to investigate the difference between endogenous and exogenous auditory attention switches and how they may be decoded differently 40 .…”
Section: Discussionmentioning
confidence: 99%